Answer:
300.29
Step-by-step explanation:
Answer:
-4
Step-by-step explanation:
So we are given the expression: | y - x | + y - 1, and we have our values for (x,y): (-3,-6).
So, we can just start plugging things in and simplifying, so:
| -6 + 3 | - 6 - 1 = | -3 | -7
= 3 - 7
= -4
Answer:
m/(1 - .8)
Step-by-step explanation:
She read 80% of her emails, which is .8 of the total. So her unread emails would be 100% - 80% = 1 - .8
that means me can be written as:
m = (1 - .8)t
where t is the total
If we solve for t, we get:
t = m/(1 - .8)
Answer:
The answer is 2/5
Step-by-step explanation:
10/15 simplified is 2/5
The answer is 45 it's the easiest